The personal MBA : a world-class business education in a single volume - Kaufman, Josh. (New York : Portfolio Penguin, 2010)
Getting an MBA is an expensive choice-one almost impossible to justify regardless of the state of the economy. Even the elite schools like Harvard and Wharton offer outdated, assembly-line programs that teach you more about PowerPoint presentations and unnecessary financial models than what it takes to run a real business. You can get better results (and save hundreds of thousands of dollars) by skipping B-school altogether. Josh Kaufman founded PersonalMBA.com as an alternative to the business school boondoggle. His blog has introduced hundreds of thousands of readers to the best business books and most powerful business concepts of all time. Now, he shares the essentials of entrepreneurship, marketing, sales, negotiation, operations, productivity, systems design, and much more, in one comprehensive volume. The Personal MBAdistills the most valuable business lessons into simple, memorable mental models that can be applied to real-world challenges.
Why read this book? -- Value creation -- Marketing -- Sales -- Value delivery -- Finance -- The human mind -- Working with yourself -- Working with others -- Understanding systems -- Analyzing systems -- Improving systems.
Includes bibliographical references and index.
Keywords: Management; Management -- Study and teaching; Business; Commerce